Maqāsid as a Parameter of the Authenticity of Hadith: a Study of Syarif Hatim Al-Auni's Thought - vikijunianto; Abdullah Faqih; Mahfudz Alfi; Anang Firdaus (Al-Bukhari : Jurnal Ilmu Hadis, 2024)
This article examines the thoughts of Syarif Hatim Al-Auni regarding maqāsid as a parameter for the authenticity of hadith. In the context of hadith studies, the issue of authenticity and authentication is a central concern that affects the acceptance and application of hadith in religious practices. This research aims to explore how maqāsid al-shariah, which refers to the fundamental objectives of shariah, can be used to assess the quality and authenticity of hadith. Using a qualitative analysis methodology, this article dissects Al-Auni's views, showing that maqāsid is not only a tool for evaluation but also a foundation for understanding the social and historical context of hadith. Syarif Hatim Al-Auni offers a new approach by using the science of maqāsid as a measure of hadith authenticity, an innovation since maqāsid is typically applied to Islamic law. This study seeks to answer two main questions, first, how does Syarif Hatim Al-Auni use maqāsid to test the authenticity of hadith, and second, what is the contribution of Al-Auni's findings. The research found that Syarif Hatim Al-Auni proposed using maqāsid not only as an approach to understand hadith but also as a parameter to determine its authenticity. Al-Auni's significant contribution lies in the expansion of the use of maqāsid, which had previously been used only to understand hadith, into a tool for determining the authenticity of hadith, based on the application of early hadith scholars that he formulated into new principles in hadith text criticism. The findings suggest that understanding maqāsid can enhance the ability of scholars and Muslims to distinguish hadith relevant to the values of justice, public benefit, and morality. This article is expected to contribute to the scholarly discourse on hadith studies and open space for new thoughts in responding to the challenges of the contemporary world.